2010
DOI: 10.1007/s00384-010-0945-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for perforated colorectal malignancy in an Asian population: an institution’s experience over 5 years

Abstract: Surgery for perforated colorectal malignancy is associated with high morbidity and mortality rates. Short-term outcome is determined by ASA score and severity of peritonitis, while long-term outcome is determined by staging of the cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
0
12
0
5
Order By: Relevance
“…Tan and associates reported that short and long term outcomes are not associated with the perforation site (13). In our series perforation was located mostly distant from the tumor.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Tan and associates reported that short and long term outcomes are not associated with the perforation site (13). In our series perforation was located mostly distant from the tumor.…”
Section: Discussionmentioning
confidence: 40%
“…Tan and associates reported that surgical intervention for liver metastases provided longterm disease-free survival (13). However our patients with liver metastasis had not only advanced disease but also presented with a bad clinical condition and all these patients died between postoperative 1st and 7th days.…”
Section: Discussionmentioning
confidence: 76%
“…Similar to cases of perforated gastric cancer, shortand long-term survival in these patients are determined by the severity of peritonitis and tumour stage, respectively [11,14].…”
Section: Perforated Colonic Adenocarcinomamentioning
confidence: 99%
“…Perforation occurs in one of two forms: it arises through the tumour itself, secondary to tumour necrosis, or it can occur at the colon proximal to the tumour as a result of ''blow-out'' of the proximal colon as a result of a closed-loop obstruction in which colonic pressure proximal to the obstructing cancer increases because of a competent ileocaecal valve ( Figures 3 and 4) [11][12][13]. Perforation occurs most commonly in the sigmoid colon and caecum [11,14]. On CT, perforated colon cancer is frequently accompanied by the formation of an abscess or fistula, and peritonitis.…”
Section: Perforated Colonic Adenocarcinomamentioning
confidence: 99%
“…If the ileocecal valve is effi cient, there is not any decompression of the dilated lumen, and the consequent severe dilatation of the colon lumen can lead to the collapse of the submucosal vascular plexus, with consequent ischemia and perforation of the wall. This severe complication can lead to a pericolic abscess if the perforation is covered by surrounding mesenteric folds or to open peritoneal perforation complicated with stercoraceous peritonitis [ 33 ].…”
Section: Obstructing Colon Cancer Complicated With Perforationmentioning
confidence: 99%